Usahatani Organik Padi Putih dan Padi Hitam: Pendekatan Pendapatan, Fungsi Produksi Cobb-Douglas dan VPM - Rahmawati, Annita; Agustono, Agustono; Adi, Raden Kunto (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This research aims to determine of (1) the productivity, income and efficiency of organic white paddy and organic black paddy and (2) the influence of production factors to production the white paddy and organic black paddy. The location of the research in Karangnyar, Central Java.The method of sampling was quota sampling with 30 respondents in each organic paddy, while the technique to collect respondents was conducted by purposive sampling. Data used in the study were primary and secondary data. Method of data analysis used in this research was (1) the analysis of productivity, income and efficiency of farming, (2) Cobb-Douglass and VPM (Varying Parameter Model) to determine the influence of factors to the production  of organik white paddy and black paddy.The results of research on the analysis of productivity of organik white paddy were 95,19 kw/ha/season and black paddy with the value of 72,53kw/ha/season. Income of organic white paddy was IDR 18,786,63.72/ha/season and income of organic black paddy with the value of IDR 25,641,526,39/ha/season. The efficiency of organic white paddy was 2,97 and the organic black paddy which was 3,83. The results of the Cobb-Douglas analysis showed the production of organic white paddy different from the organic black paddy.  VPM showed that the production factor of land area and labor significantly influenced production in organic white rice and organic black rice farming, while seeds and manure were known to only have significant influence toward production in organic white rice.